Pemberdayaan Kelompok Sadar Wisata (Pokdarwis) Tiram Tambun Dalam Pengembangan Usaha Homestay Di Desa Wisata Mentawir Kabupaten Panajam Paser Utara - Yogiana Mulyani; Ranti Rustika; Henry Winnarko; Tri Retno Nugroho (ISAS (Indonesian Society of Applied Science), 2021)
The management of Mentawir Tourism Village in Panajam Paser Utara Regency is carried out by community who are the members of the Tiram Tambun Tourism Awareness Group. In developing Mentawir Tourism Village, one of the requirements that must be fulfilled is the availability of accommodation or lodging facilities in the form of a homestay. Tiram Tambun has started to develop several houses to be used as homestays. However, the lack of knowledge and skills about the homestay causes the management to be not optimal. Therefore, in this community service activity, training and assistance were given to Tiram Tambun regarding homestay management. The results of this activity are in the form of increased insight and knowledge also skills about homestay management. This is indicated by the addition of the number of homestays and the existence of efforts to meet several standard homestay criteria.